In situ synthesis of fluorescent polydopamine nanoparticles coupled with enzyme-controlled dissolution of MnO2 nanoflakes for a sensitive immunoassay of cancer biomarkers. Issue 43 (23rd October 2017) - Lin, Zhenzhen; Li, Meijin; Lv, Shuzhen; Zhang, Kangyao; Lu, Minghua; Tang, Dianping
Abstract : A new fluorescence/visual immunosensing strategy was designed for the AFP detection coupling enzyme-controlled formation of polydopamine and dissolution of MnO2 nanoflakes. Abstract : Herein, a novel immunosensing strategy was designed for the sensitive fluorescence/visual detection of alpha-fetoprotein (AFP), by combining the enzyme-controlled formation of polydopamine (PDA) nanoparticles with the dissolution of manganese dioxide (MnO2 ) nanoflakes. Initially, a sandwich-type immunoreaction was fabricated on a capture antibody-coated microplate by using detection antibody/ascorbate oxidase-conjugating gold nanoparticles (AO X –AuNP–Ab2 ) as the detection probe. The ascorbate oxidase, carried within the immunocomplex, oxidized ascorbic acid (AA) to dehydroascorbic acid (DAA) to inhibit the dissolution of the MnO2 nanoflakes. This resulted in an increment in fluorescent PDA nanoparticles from the oxidation of dopamine (DA) into its quinone derivative with the aid of the MnO2 nanoflakes. Under optimal conditions, the fluorescence intensity of the PDA nanoparticles increased with increasing AFP concentration within the dynamic working range of 0.05–20 ng mL −1, with a detection limit (LOD) of 17.3 pg mL −1 . The sensor also showed high specificity and acceptable accuracy for the detection of target AFP against other potential cancer biomarkers. Importantly, this study demonstrated for the first time that fluorescent PDA nanoparticles could be used as signal-generation tags and applied to an enzyme immunoassay. Although this methodology focused on AFP detection, it would be suitable for the detection of other cancer biomarkers if the corresponding antibodies were employed.